Feeding preferences of Phylloicus sp. (Trichoptera: Calamoceratidae) in a Neotropical river of the Sierra Nevada de Santa Marta, Colombia - Tamaris-Turizo, Cesar E.; Gómez-Arrieta, Katty; Pinilla-A., Gabriel A. (Revista de Biología Tropical, 2020)
Introduction: Fragmentation of allochthonous material by aquatic insects is a functional process that has been little studied in Colombian rivers. One of the most abundant shredder genus in American tropical stream ecosystems is the caddisfly genus Phylloicus (Calamoceratidae). Objective: in this study we evaluate the effect of chemical (nitrogen, phosphorus and lignin) and physical (toughness) attributes of leaves of three dominant tree species (Ficus tonduzii, Zygia longifolia and Clusia multiflora) in the riverine area of the middle section of the Gaira river, on leaf preferences and larval growth of a species of Phylloicus. Methods: multiple food selection field experiments were performed, in which experimental chambers were located in the river for twenty-one days. For the assessment of leaf quality, leaves were collected in the river, dried and pulverized to perform chemical analyzes. Results: there were no significant differences in lignin and phosphorous percentages between the leaves of the three species, but nitrogen content and leaf toughness differed among them. The leaves of C. multiflora were softer (180.1± 53.9 g) than those of F. tonduzii (285.3 ± 88.4 g) and Z. longifolia (232.3 ± 60.8 g), but without differences between the last two species. The Z. longifolia leaves also had more nitrogen (1.9 ± 0.0 %) than those of the other species (1 ± 0.0 %). Regarding leaf selection, Phylloicus sp. larvae used in greater proportion the leaves of C. multiflora. Although lignin and phosphorous differences were not significant, the leaves of C. multiflora had lower toughness, which could make them more palatable for Phylloicus sp. On the other hand, the daily specific growth of the larvae was higher when they used leaves of F. tonduzii. Conclusions: our findings seem to indicate that the most preferred leaves were not necessarily those of better nutritional quality and suggest that leaf toughness was the most important variable in the selection of leaf litter by the larvae of Phylloicus sp.